Il-4/13a and Its Receptor System in Atlantic Salmon (Salmo Solar): Upregulation of Key Genes Involved in Adaptive Immunity - Imarai-Bahamonde, C; Maisey-Munoz, K; Montero, R (Academic Press, 2019)
Sin Resumen Disponible